A PROPULSION AND GUIDANCE SYSTEM FOR THE CONTROLLED DESCENT OF A LOW-COST CANSAT - Lucchese Vides, Dario Oscar; Mario Ricardo Amani; Mario José Agustín Díaz; Egea Rubén Darío; Ricardo Medel; Andrés Pienizzio; José Luis Ruiz (Revista Interdisciplinar de Pesquisa em Engenharia, 2025)
CanSats are non-orbital satellite models used for education under a STEM (Science, Technology, Engineering, and Mathematics) educational approach. This device promotes scientific and technological interest by providing hands-on learning in space science and technology. During CanSat contests, teams of students reproduce the process of satellite design, manufacturing, testing, launch, and operation at a small scale. Originally proposed in 1991 in the USA and Japan, the first educational use of CanSats in Argentina dates back to 2004, but only recently country-wide CanSat contests were carried out by the Ministry of Science, Technology, and Innovation (MINCYT) and the National Commission for Space Activities (CONAE). During one of these contests, a team of students and faculty from the Aguilares Technical Institute of the National University of Tucumán proposed a CanSat design to capture images of burned crop surfaces, a common environmental problem in Tucumán Province. In order to cover larger and specific areas for such recordings, the CanSat had to be controlled from the Ground Station by using a servo-controlled parawing, a 3D-printed propeller, and a two-way communications subsystem based on LoRa technology. These subsystems are rarely found at CanSat designs, and there is no bibliographic record of a design including all of the three characteristics. The team’s success in coping with the complexity of the proposal resulted in them winning the "Best Technical Development" award. In this work we cover the novel design of the CanSat and its challenges, by showing the different subsystems required for achieving the primary and secondary missions.